Efficiency of self‐assembled etoricoxib containing polyelectrolyte complex stabilized cubic nanoparticles against human cancer cells. Issue 1 (31st May 2020) - Malviya, Rishabha; Sharma, Pramod Kumar; Dubey, Susheel Kumar
Abstract: Introduction: The aim of the present research was to formulate chitosan‐kheri gum polyelectrolyte complex (CKGPEC) stabilized etoricoxib containing cubic nanoparticles and evaluate against various human cancer cell lines. Methods: The novel solvent‐antisolvent method was utilized for the fabrication of nanoparticles using CKGPEC as a stabilizer. 3 2 factorial designs were applied to investigate the effect of concentration of chitosan (Ch) and kheri gum (KG) over entrapment efficiency and size of nanoparticles. Nanoparticles were characterized and evaluated against the human breast cancer cell line (MCF7), human colon cancer cell line (HT‐29), and human skin cancer cell lines (SK‐MEL‐2). Results: It was observed that the concentration of Ch and KG significantly affects the entrapment efficiency and size of nanoparticles. The entrapment efficiency of nanoparticles was found in the range of 70.21 ± 0.42% (K4) to 82.77 ± 0.29% (K6) while the size was observed 79.3 nm (K5) to 490.1 nm (K1). SEM clearly showed the cubic shape of nanoparticles. All the formulations followed Baker‐Lonsdale kinetic model of drug release. The utilization of the egg membrane and tomato membrane as a biological barrier was not altering the release kinetics of the drug. Prepared nanoparticles were found to be effective against various human cancer cells but the better effect was observed against SK‐MEL‐2 cells than MCF‐7 cells, followed by HT‐29 cell in in vitro conditions. Discussion: Taken together, it can be concluded that Ch‐KG PEC stabilized nanoparticles were successfully formulated and could be utilized against various human cancer. In future clinical studies could be performed for the exact determination of therapeutic potential.